2019
DOI: 10.1093/bioinformatics/btz062
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of accurate interatomic contact surface areas for the quantitative analysis of non-bonded molecular interactions

Abstract: Summary Intra- and intermolecular contact surfaces are routinely calculated for a large array of applications in bioinformatics but are typically approximated from differential solvent accessible surface area calculations and not calculated directly. These approximations do not properly take the effects of neighboring atoms into account and tend to deviate considerably from the true contact surface. We implemented an extension of the original Shrake-Rupley algorithm to accurately estimate int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 16 publications
0
61
0
Order By: Relevance
“…Secondary structure was assigned using STRIDE (Frishman & Argos, 1995); Poisson–Boltzmann electrostatic calculations were performed using APBS/PDB2PQR (Jurrus et al , 2018); protein–protein interfaces were analyzed using PISA (Krissinel & Henrick, 2007), PIC (Tina et al , 2007) and the AnalyseComplex command of FoldX (Delgado et al , 2019); intermolecular contact surface areas were calculated with dr_sasa (Ribeiro et al , 2019). Structural figures and movies were generated with PyMOL (Schrödinger, LLC), UCSF Chimera (Pettersen et al , 2004)/ChimeraX (Goddard et al , 2018) and Illustrate (Goodsell et al , 2019); unless otherwise specified, they were based on the refined coordinates of UMOD fl .…”
Section: Methodsmentioning
confidence: 99%
“…Secondary structure was assigned using STRIDE (Frishman & Argos, 1995); Poisson–Boltzmann electrostatic calculations were performed using APBS/PDB2PQR (Jurrus et al , 2018); protein–protein interfaces were analyzed using PISA (Krissinel & Henrick, 2007), PIC (Tina et al , 2007) and the AnalyseComplex command of FoldX (Delgado et al , 2019); intermolecular contact surface areas were calculated with dr_sasa (Ribeiro et al , 2019). Structural figures and movies were generated with PyMOL (Schrödinger, LLC), UCSF Chimera (Pettersen et al , 2004)/ChimeraX (Goddard et al , 2018) and Illustrate (Goodsell et al , 2019); unless otherwise specified, they were based on the refined coordinates of UMOD fl .…”
Section: Methodsmentioning
confidence: 99%
“…The total accessible surface area of the 71 amino acid residue a-neurotoxin of N. siamensis, venom (PDB 1CTX; alphacobratoxin from Naja siamensis) is calculated to be about 5,206 sq. Å using a program described by Ribeiro et al (89).…”
Section: A Quest For Universal Pdav Against All the Neurotoxic Elapid Snakesmentioning
confidence: 99%
“…Recent reverse docking study revealed that Autodock vina is biased (shows negative correlation) due to the contact surface area [ 28 ]. Therefore, we measured the protein–compound contact surface area [ 29 ] and normalized for the number of the molecular docking-involved atoms. We also evaluated the peptide model quality applying DOPE (discrete optimized protein energy) [ 30 ] because we obtained structures from the modeling web server.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, we designed a new custom score for intrinsically disordered region direct targeting drug discovery evaluation, combining all the aforementioned scores. where is the smina (Autodock vina) score function [ 28 ], is the DOPE score function [ 30 ], and is protein–compound contact surface area calculation algorithm (dr_sasa) score [ 29 ]. Normalization of the dr_sasa score with the molecular docking-involved atom number ( n ) was empirical adjustment to calculate atomic contribution.…”
Section: Methodsmentioning
confidence: 99%